2017
DOI: 10.1016/j.jbo.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Experience of total scapular excision for musculoskeletal tumor and reconstruction in eastern Asian countries

Abstract: Total scapulectomy and reconstruction has been performed for scapular tumor, however, most of the reconstruction methods have resulted in poor functional outcomes and there is still room for improvement. Most of the reports of reconstruction after scapulectomy are from a single institution. In the present study, we investigated functional outcomes after total scapulectomy in a multicenter study in The Eastern Asian Musculoskeletal Oncology Group (EAMOG). Thirty-three patients who underwent total scapulectomy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In that same study, nearly half of patients with scapular replacement had greater than 40 degrees of abduction and forward flexion. In 2017, Hayashi et al mirrored those results in a multicenter study preformed at Eastern Asian Musculoskeletal Oncology Group [18]. Based on Ennekin functional scores, prothesis resulted in improved functional outcomes compared to suspension (23.6 versus 21.4).…”
Section: Discussionmentioning
confidence: 99%
“…In that same study, nearly half of patients with scapular replacement had greater than 40 degrees of abduction and forward flexion. In 2017, Hayashi et al mirrored those results in a multicenter study preformed at Eastern Asian Musculoskeletal Oncology Group [18]. Based on Ennekin functional scores, prothesis resulted in improved functional outcomes compared to suspension (23.6 versus 21.4).…”
Section: Discussionmentioning
confidence: 99%
“…Scapular endoprostheses is another option, as long as the rhomboids, latissimus dorsi, deltoid, and trapezius muscles are preserved 11 . A recent study comparing these methods showed superior functional result from prosthesis or recycled bone 12 …”
Section: Discussionmentioning
confidence: 99%
“…With its insertion and innervation left intact, the LDMC was rotated superiorly to achieve 2 goals: to cover the posterior defect and to provide a dynamic superior pull to the humerus. The LDMC had been used in a similar fashion in 2 oncological reconstruction cases using custom made scapular endoprosthesis 12 . An ALT flap was used to cover the large anterior soft tissue defect, including the TFL muscle as a functional muscle transfer, to provide secondary dynamic support to the shoulder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall postoperative survival rate was 88.2% (15/17), and the disease-free survival rate was 70.6% (12/17). In addition, several studies have shown that prosthetic reconstruction can obtain better shoulder joint function and shape than humeral suspension [ 22 , 23 ]. Pritsch et al [ 12 ] included 32 patients who had total scapulectomies (reconstructions with humeral suspensions in 16 patients and scapular endoprostheses in 16 patients), and the results showed that scapular endoprosthetic reconstruction led to better functional and cosmetic results than humeral suspension.…”
Section: Discussionmentioning
confidence: 99%